2017
DOI: 10.1186/s12917-017-1030-7
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 protein expression and tumor associated inflammatory cells (macrophages and mast cells) in canine colorectal carcinoma

Abstract: BackgroundKi67 index, tumor associated macrophages (TAMs) and mast cells (MCs) are associated with malignancies in animal and human neoplasms including colorectal carcinomas (CRC). This has not been assessed in canine CRC. Given similar genetic abnormalities between human and canine CRC, we assessed Ki-67 and mitotic indices, TAMs and MC count (MCC) in canine CRC (n = 17). TAMs and MCC were compared with those in adenomas (n = 13) and control (n = 9).ResultsKi-67 index in CRC (17.13 ± 11.50) was strongly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The interest in TAMs has been also increasing in veterinary oncology where studies have mainly focused on mammary carcinomas and on colorectal carcinoma [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in TAMs has been also increasing in veterinary oncology where studies have mainly focused on mammary carcinomas and on colorectal carcinoma [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Slow growth of CAA corresponds to the low numbers of Ki-67-positive cells found in this neoplasm, which is in contrast to COSCC, with high Ki-67 expression. The Ki-67 labeling index is considered to be a prognostic factor of many canine cancers [32][33][34][35], and, in COSCC, it was significantly associated with a lymph node metastasis [36]. Ki-67 expression might be also a negative prognostic marker for human patients with OSCC [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results also showed a positive correlation between plasma C-MYC level and Ki67 index. It has been reported that the protein Ki67 is expressed in the nucleus of cycling cells and used to measure the activity of cell proliferation [47][48][49]. Ki67 index is recognized as an independent prognostic factor in breast cancer [50][51][52][53][54], high Ki67 index is associated with a poor prognosis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%